Unusual Presentation of Pleural Space Ascariasis Infection from Eastern Sudan: A Case Report - Mohammed NA; Adam AO; Osman MAH; Abass HM; Salih AM; Abaker AAM; Mustafa A; Magoub M (Dove Medical Press, 2024)
Nader Ahmed Mohammed,1 Abdulrahman OE Adam,2 Monzir Ahmed Hassan Osman,2,3 Hibatallah MA Abass,2,3 Awad MA Salih,2,3 Ameer AM Abaker,2,3 Alamin Mustafa,3,4 Mamoun Magoub5 1Department of Medicine, Faculty of Medicine, University of Kassala, Kassala, Sudan; 2Faculty of Medicine, Omdurman Islamic University, Omdurman, Sudan; 3Patient Support Organization Research Unit, Khartoum, Sudan; 4Faculty of Medicine, Al-Neelain University, Khartoum, Sudan; 5Department of Microbiology & Parasitology, Faculty of Medicine & Health Science, West Bank of Gash River, University of Kassala, Kassala, SudanCorrespondence: Mamoun Magoub, Department of Microbiology & Parasitology, Faculty of Medicine & Health Science, West Bank of Gash River, University of Kassala, Kassala, Sudan, Tel +24991291999, Email mamounmagzoub@kassalauni.edu.sd Alamin Mustafa, Faculty of Medicine, Al-Neelain University, JG37+2RM, 52nd St, Khartoum, Sudan, Tel +249902612984, Email alamin900005@gmail.comBackground: Ascaris lumbricoides is a common infectious parasite of the gastrointestinal tract worldwide, but the invasion of the pleural cavity is rare.Case Report: A 45-year-old man from Eastern Sudan presented to the emergency department complaining of breathlessness, cough stained with blood, and chest pain one month before his presentation. Also, he complained of high-grade fever for two weeks associated with sweating. Diagnosis of hydropneumothorax was made and a chest tube was inserted, two days later we found three adult A. lumbricoides worms in the chest drain.Conclusion: The patient was treated with Albendazole 200 mg, orally twice, daily for seven days, he improved and was referred to a cardiothoracic surgeon for more assessment. Our study highlights that internal medicine specialists should know about pleural ascariasis when patients present with respiratory signs and symptoms, especially in A. lumbricoides endemic regions like Eastern Sudan.Keywords: neglectable tropical diseases, pulmonology, pleural cavity, ascariasis, Ascaris ...